2014
DOI: 10.1002/2014jd022080
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between continuing current and positive leader growth

Abstract: It has long been speculated that the source of continuing current (CC) for a negative cloud-to-ground flash is provided by the growth of its positive leader into negative charge regions. In this study, data from the Langmuir Electric Field Array (LEFA) and Lightning Mapping Array (LMA) are used to investigate these speculations. LEFA and LMA data provide a way to estimate the occurrence and duration of CC and channel growth throughout a flash, respectively. By connecting LMA VHF sources onto contiguous channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 21 publications
3
37
0
Order By: Relevance
“…The flash that we study occurred on 8 July 2013 at 20:28:56 UTC (Figure 10 of Lapierre et al [] and Figures and of the present study). This flash produced seven strokes along two channels to ground, as evidenced by the occurrence of two stepped leaders seen in Figure (highlighted in green before events 1 and 3).…”
Section: Analysis and Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The flash that we study occurred on 8 July 2013 at 20:28:56 UTC (Figure 10 of Lapierre et al [] and Figures and of the present study). This flash produced seven strokes along two channels to ground, as evidenced by the occurrence of two stepped leaders seen in Figure (highlighted in green before events 1 and 3).…”
Section: Analysis and Discussionsupporting
confidence: 91%
“…The NLDN data (colored triangles in a and vertical lines in b) detected a strong, +94 kA +CG 125 ms into the flash (event 2 in ). The occurrence of the +CG stroke was confirmed by the LEFA data (b, middle), whose monopolar field change following the stroke at the multiple LEFA stations (see Figure ) [ Lapierre et al , ] indicated a +CC of about 70 ms duration (gray shaded area). Typical of +CGs, the leader to ground was not detected by the LMA, due to being weakly radiating and masked by the ongoing negative breakdown in the storm.…”
Section: Analysis and Discussionmentioning
confidence: 99%
See 3 more Smart Citations